Mediating Role of Psychological Contract in the Relationship between Workplace Spirituality and Affective Commitment - Ashfaq, Muhammad; Muhammad Imran Qureshi, Dr; Irum, Sobia; Fadillah Ismail, Dr; Rabeatul Husna, Dr (International Journal of Engineering and Technology, 2018)
Malaysian banking sector is facing commitment challenge of their employees especially in the current highly competitive business environment. Now banks want to retain and engage their competent employees so there is a need to create or enhance their affective commitment because this affective commitment is a key to retain and engage competent employees. Previous research explains that effective commitment provide employees emotional attachment with their organisation so there is a need to explore those factors through which organisations can develop the affective commitment of their employees. Healthy amount of research has been conducted to deal with employee attitude and commitment. As time goes on new concepts are coming up with new management ideas. One such new area of research is workplace spirituality. Previous research in this field discovered numerous benefits of workplace spirituality to the organization and employee as well as organizational and employee development, and commitment. Literature review pointed out that Malaysian banking sector is facing the problem of employee commitment. Present research is an attempt to deal this problem of employee commitment with the help of workplace spirituality along with psychological contract as a mediator. Subjects for this research were 350 bank employees working in commercial banks in Malaysia. Structural equation modelling SEM â€“ PLS was the main statistical technique utilized in this study. All the main relationships were found to have significant effect on employees affective commitment, Overall, the results indicate that the model provide good understanding of the workplace spiritualityâ€™s influence on employees commitment in banking sector of Malaysia. Â Â